The Effect of Organic Growing Media and Amino Acid Fertiliser Application on the Growth of Arabica Coffee (Coffea Arabica) Seedlings - Roganda Tambunan; Sri Mahareni Br Sitepu; Andi Setiawan (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Seedling quality is a determining factor in the success of arabica coffee cultivation. This study aimed to examine the effect of organic planting media and amino acid fertilizer on the growth of arabica coffee seedlings (Coffea arabica) Sigarar Utang variety. The research was conducted at the experimental field of the Agrotechnology Study Program, Pancabudi Development University, Glugur Rimbun Village using a factorial Randomized Block Design (RBD) with two factors. The first factor was organic planting media composition (chicken manure and topsoil) with four levels: M0 (control), M1 (150 grams), M2 (300 grams), and M3 (450 grams). The second factor was amino acid fertilizer dosage with four levels: A0 (control), A1 (2 grams/liter), A2 (4 grams/liter), and A3 (6 grams/liter), resulting in 16 treatment combinations with 3 replications. Parameters observed included plant height, stem diameter, leaf number, root length, and root volume at 4, 8, and 12 weeks after planting. Results showed that the M3A3 combination treatment (450 grams organic media + 6 grams/liter amino acid fertilizer) provided the best results for all observation parameters at 12 weeks with plant height of 18.083 cm, stem diameter of 2.742 mm, and leaf number of 13.417 leaves. This research contributes to developing quality and sustainable arabica coffee seedling techniques to support national coffee productivity.